NEEDS OF ESP LEARNERS (Multidisciplinary Journal of Science and Technology, 2025)
English for Specific Purposes (ESP) has emerged as a response to the increasing global demand for professionally or academically tailored language instruction. ESP is built upon the premise that language learning is most effective when it is relevant to learners’ specific goals and contexts. This paper explores the nature of ESP learners’ needs, how they are identified, and their implications for curriculum design and pedagogy. Drawing on theoretical models and practical case studies, the discussion highlights the importance of conducting thorough needs analysis and continuously aligning instruction with learners’ real-world communication tasks.